(untitled) (Revista Internacional de Folkcomunicação, 2023)
The article seeks to review the epistemological foundations that allowed the emergence of Folkcommunication, formulated in the 1960s by Luiz Beltrão, from the folklore studies. More specifically with one of its aspects: the dialectic folkloristics, whose great exponent was Edison Carneiro and who had the readings of Antônio Gramsci as a matrix of thought. In this work, we explore the various possible understandings for the term folklore – demarcating, in the process, our working definition. Then we discuss the reasons why certain terms proposed as substitutes are insufficient to account for the scope of the phenomenon. Finally, we outline the similarities between Carneiro and Beltrão, showing how the sensibilities evoked by this text are not foreign to the field of Communication: the understanding of traditional popular culture as an element of criticism and commentary, resistance and transformation.